2022
DOI: 10.1177/08944393211056229
|View full text |Cite
|
Sign up to set email alerts
|

Item Nonresponse in Web Versus Other Survey Modes: A Systematic Review and Meta-Analysis

Abstract: Nonresponse is a fundamental issue in survey research, due to the trend of declining response rates across survey modes. This issue is particularly serious for web surveys: A recent meta-analysis found that unit nonresponse in web surveys is, on average, higher by 12 percentage points than in other modes ( Daikeler et al., 2020 ). Although the issue of unit nonresponse in web and other survey modes has been investigated in several meta-analyses, item nonresponse has not been examined meta-analytically, a gap a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 66 publications
1
8
0
Order By: Relevance
“…As such, the majority of the students did not participate in this exercise. This trend of result reflects the outcome of recent studies that have reported unit non-response as a common phenomenon in online surveys ( Marcham et al, 2020 ; Čehovin et al, 2022 ; Falk and Thies, 2022 ; Plante et al, 2022 ). Nevertheless, the recorded high unit non-response rates in this context cannot be entirely attributed to the transition from a paper-and-pencil survey to an online survey.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…As such, the majority of the students did not participate in this exercise. This trend of result reflects the outcome of recent studies that have reported unit non-response as a common phenomenon in online surveys ( Marcham et al, 2020 ; Čehovin et al, 2022 ; Falk and Thies, 2022 ; Plante et al, 2022 ). Nevertheless, the recorded high unit non-response rates in this context cannot be entirely attributed to the transition from a paper-and-pencil survey to an online survey.…”
Section: Discussionsupporting
confidence: 79%
“…This transition has also led to decreased rates of student participation, resulting in high rates of non-response ( Dillman et al, 2002 ). Several studies have shown that unit non-response (i.e., individuals not responding to any item on the survey instrument or complete non-participation) in online evaluation surveys is a key challenge for the introduction of technology in students’ appraisal of teaching and learning ( Guder and Malliaris, 2013 ; Marcham et al, 2020 ; Čehovin et al, 2022 ; Falk and Thies, 2022 ; Plante et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the results are only based on the responses among Chinese college students, therefore its application in other groups or areas needs to be examined. Third, online self-report questionnaires were applied, which may result in unreliability and inaccuracy because of the inherent drawbacks of self-reporting (i.e., recall bias, over- or under-reporting, non-response error, and social desirability) ( 118 , 119 ). Fourth, it was valuable that the findings give new insights into the antecedents of behavior intention (>60%), yet the whole model only explained 6% of PA, hinting that more components and covariates need to be identified in the future (e.g., volitional factors between intention and behavior) ( 120 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another study found that an interviewer led survey had lower item nonresponse than PC or Webbased survey designs (Lee et al 2019). A more recent meta-analysis of item nonresponse in Web versus other modes found no statistically significant difference in the average item nonresponse rate in Web versus other survey modes (Čehovin, Bosnjak, and Lozar Manfreda 2022).…”
Section: Introductionmentioning
confidence: 99%